ANALISIS PERILAKU TERHADAP SIKAP PENCEGAHAN INFEKSI MENULAR SEKSUAL PADA REMAJA DI DESA NEGERI BARU KETAPANG - Sri Rahayu; Dewi Elliana; Widia Anggreani (Midwifery Care Journal, 2021)
Adolescents are the age group with the highest number of STIs compared to other age groups. The high number of people with STIs in adolescents and the younger generation really needs our attention because of the dangers and broad impacts. The highest number of STIs cases among adolescents in June 2019 was 29 cases of HIV-AIDS. The purpose of the study was to determine the effect of behavior on attitudes regarding the prevention of sexually transmitted infections (STIs) in adolescents.This research study is descriptive with a questionnaire interview survey of 25 respondents with simple regression analysis. Results: the behavioral variable has the lowest score of 9 and the highest score of 15. With an average value of the behavioral variable of 13.08 with a standard deviation of 1.352 and the value of the STIs prevention attitude variable in adolescents is 46.16 with a standard deviation of 3.923. And STIs prevention attitude variable in adolescents has the lowest score of 37 and the highest score of 54. The average value of the STIs prevention attitude variable in adolescents is 46.16 with a standard deviation of 3.923. Based on the results of the t test, the t-count value is 2.181 with a sig value of 0.040. In this study, the results of the t test are significant. Conclusion: there is an influence of behavior on adolescent attitudes in preventing STIs. Suggestions increase knowledge about STIs in all adolescents.